Carotid intima-media thickness and cardiovascular risk factors in childhood and adolescent obesity - Mahfouz, Aml A.; Massoud, Mohamed N.; Omar, Omneya M.; Abou–Gabal, Ahmed M. (International Journal Of Community Medicine And Public Health, 2018)
Background: Childhood obesity is a significant health problem that has reached epidemic proportions around the world and it is a risk factor for atherosclerosis. The study aimed to investigate carotid intima-media thickness (CIMT) in obese children and evaluate the relationship of CIMT to various cardiovascular risk factors. Methods: This was achieved through including 40 obese children aged 5-16 years who were referred to Alexandria University Children's Hospital (AUCH) and 20 non-obese age and sex-matched children as the control group. All obese children in this study were subjected to thorough history taking, thorough clinical examination stressing on anthropometric measurement, blood pressure measurement and laboratory investigations including lipid profile, liver function tests, fasting glucose and fasting insulin and ultrasonographic study for the liver and carotid intima-media thickness measurement. Results: compared to the control, the obese children demonstrated a significantly thicker carotid intima-media (p<0.001). Univariate correlation analysis revealed that CIMT was significantly correlated with the body mass index (BMI), waist circumference measurement, diastolic blood pressure (DBP), high-density lipoprotein cholesterol (HDLC), fasting insulin, homeostasis model assessment- insulin resistance (HOMA-IR), quantitative insulin-sensitivity check index (QUICKI) and fatty liver. In multiple linear regression analysis, CIMT correlated significantly with DBP in the obese group. Conclusions: Atherosclerosis begins in obese children and adolescents and CIMT measurement is a noninvasive, feasible, reliable and inexpensive method to detect subclinical atherosclerosis.